The Judiciary - CHAN, Gary Kok Yew (Institutional Knowledge at Singapore Management University, 2015)
The Judiciary forms an indispensable third pillar of the Government, in addition to the Executive and the Legislature. Under the principle of separation of powers, it is meant to serve as a check on the other two branches of government. Through the roles it discharges in the adjudication of disputes and the overall administration of justice in Singapore, the potential impact and contribution of the Judiciary are indeed extensive and profound, affecting not merely the common man in the street and the business community but also the society at large.